Efficacy of Herbal Medicines Intervention for Colorectal Cancer Patients With Chemotherapy-Induced Gastrointestinal Toxicity — a Systematic Review and Meta-Analysis - Chen, Yuanyuan; Cheng, Chien-shan; Tan, Hor-Yue; Tam, Chi Wing; Wang, Ning; Feng, Yibin (Frontiers in Oncology, 2021)
Purpose: Chemotherapy-induced gastrointestinal (CIGI) toxicity affects colorectal cancer patients’ quality of life and the clinical application of treatment drugs. This review aims to evaluate the efficacy of traditional herbal medicines (HMs) in alleviating symptoms of CIGI toxicity (including nausea and vomiting, anorexia, diarrhoea, constipation, oral mucositis, abdominal pain, and abdominal distension), and to explore further individual herb or herbal combinations in alleviating the CIGI toxicity. Methods: Nine electronic databases were screened from 2010 to 2020. Twenty-two randomized controlled trials with a total of 1995 patients evaluating the complementary efficacy of HMs with chemotherapy compared with chemotherapy-alone were included. Further sensitivity analyses of orally administered multi-ingredient HM interventions were explored based on the HM interventions’ composition. Results: The meta-analysis showed that HM treatment combined with chemotherapy significantly alleviated overall CIGI toxicity (RR=0.78 [0.72, 0.84], P<0.001, I2 =44%), nausea and vomiting (RR=0.74 [0.66, 0.82], P < 0.001, I2=35%), diarrhoea (P = 0.02, RR = 0.64, 95%CI = 0.44 to 0.93, I2=50%), oral mucositis (RR=0.65 [0.48, 0.88], P =0.005, I2=24%), and abdominal distension (RR=0.36 [0.18, 0.73], P=0.004, I2=0%). However, no statistically significant effects of HMs were shown in studies with a double-blind design for CIGI toxicity. Based on the ingredients of the HMs, further sensitivity analyses identified five herbs (Glycyrrhiza uralensis Fisch., Atractylodes macrocephala Koidz., Astragalus membranaceus (Fisch.) Bge., Codonopsis pilosula (Franch.) Nannf., and the pericarp of Citrus reticulata Blanco.) that were associated with significant reductions in CIGI toxicity. Conclusion: A statistically significant effect of HMs combined with chemotherapy on alleviating overall CIGI toxicity, nausea and vomiting, diarrhoea, oral mucositis, or abdominal distension is only shown in studies without a double-blind design. Further well-designed, double-blinded, large-scaled RCTs are warranted to comprehensively evaluate the treatment efficacy. Further clinical research including the five herbs to chemotherapy in patients, and the potential synergistic effects of the combinations of these herbs should be conducted.